FEATURES OF LANDING APPROACH FOR AIRCRAFT IN AUTOMATIC AND YOKE CONTROL MODES IN CONDITIONS OF HORIZONTAL LATERAL WIND SHEAR - Polukhin, А. V.; Ostapenko, O. S. (Science-based technologies, 2019)
World statistics show that about 36% of all accidents in aviation transport take place at the landing approach and landing stages. If you take into account that their average duration does not exceed 3-4% of the average flight time, the flight safety level at these stages is tens of times lower than the safety level throughout the flight It’s been shown that flight safety provision for aircraft in landing approach and landing stages under wind shear conditions is important and crucial issue and requires deep research. Flight dynamics research has been conducted for mid-range aircraft at landing approach stage under horizontal lateral wind shear conditions.